Life Satisfaction and Economic Conditions in East and West Germany Pre- and Post-Unification - Richard A. Easterlin; Anke C. Zimmermann (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
Economic disruption in East Germany at the time of unification resulted in a noticeable drop in life satisfaction. By the late 1990s East Germany's life satisfaction had recovered to about its 1990 level, and its shortfall relative to West Germany was slightly less than that before unification. In West Germany life satisfaction was fairly constant before unification, but subsequently trended moderately downward, with Turkish life satisfaction declining noticeably relative to Germans. Changes in life satisfaction in East and West Germany both for Germans and foreigners are most closely associated with relative income variables, not absolute income.
Keywords: D31; D60; I31; O52; P3; 330; Life satisfaction; happiness; relative income; income satisfaction; transition economies